Art therapy to reduce burnout and mental distress in healthcare professionals in acute hospitals: a randomised controlled trial - Paul Bassett; Stefan Priebe; Gehan Soosaipillai; Dennis Ougrin; Megan Tjasink; Catherine Elizabeth Carr (BMJ Public Health, 2025)
Introduction Burnout and mental distress are prevalent among healthcare professionals (HCPs), particularly in acute hospital settings. This study evaluated the effectiveness of a structured group art therapy intervention in reducing burnout and associated mental distress in HCPs.Methods We conducted a multicentre, unblinded, randomised, parallel assignment, waitlist-controlled trial in four National Health Service secondary care hospitals in London, UK, between 4 May 2023 and 5 March 2024. A total of 129 HCPs with moderate-to-severe risk of burnout or levels of perceived stress were randomly assigned to either group art therapy (6 weekly 90-min sessions) or a waitlist control.The primary outcome was change in emotional exhaustion as a core dimension of burnout, measured using the Maslach Burnout Inventory-Human Services Survey. Secondary outcomes were the other two burnout dimensions: depersonalisation and personal accomplishment, as well as perceived stress, measured on the perceived stress scale, anxiety, assessed on the generalised anxiety disorder seven-item scale, and depression, measured on the eight-item patient health questionnaire depression scale. Outcomes were assessed at baseline and 6 weeks postintervention/control period. Intervention group outcomes were also assessed at 3-month follow-up.Results Primary outcome data were obtained from 115 (89%) of 129 participants, who represented a range of clinical specialties and professions. Emotional exhaustion scores were significantly lower in the intervention group compared with the control group at 6 weeks (adjusted mean difference: 4.8; 95% CI 2.4 to 7.3; p<0.001). Significantly more favourable scores were also found in depersonalisation, perceived stress, anxiety and depression in the intervention group. Gains were sustained at 3-month follow-up.Conclusions Six weekly sessions of group art therapy can significantly reduce burnout risk and mental distress in HCPs from different professional backgrounds in acute hospital settings. Wider implementation of the intervention should be considered.Trial registration number ClinicalTrials.gov ID: NCT05728086.